Comparing movement imagery and action observation as techniques to increase imagery ability. (September 2019) - Williams, Sarah E.
Abstract: Objectives: This study compared the effectiveness of an imagery intervention with an action observation intervention on the effectiveness of improving the ability to image different content and characteristics. These two intervention techniques were also compared to a control condition. Design: Experimental study, random assignment to one of three groups and repeated assessments. Method: Participants (N = 51; 59% female; M age = 19.37, SD  = 1.33) were randomly assigned to one of three intervention groups: 1) imagery, 2) observation, 3) control. Imagery ability was assessed using the Movement Imagery Questionnaire-3 (MIQ-3) and Sport Imagery Ability Questionnaire (SIAQ) before and after the 4-week intervention. Groups consisted of either imaging a series of finger exercises (imagery group), observing videos of the same exercises (observation group), or performing the stroop task (control group). The intervention was conducted once a week in the lab, and imagery and observation interventions were also performed in participants' own time between visits. Results: Participants in the imagery and observation groups experienced a significant increase in their SIAQ skill, strategy, and mastery imagery ability from baseline to post intervention ( p s < .05); the control group experienced no change in their imagery ability of these subscales. All groups experienced an increase in their MIQ-3 external visual imagery from baseline to post intervention. 82% of the observation group experienced spontaneous imagery during observation of the movements. Conclusions: Imagery and observation are similarly effective intervention strategies in improving movement based imagery ability. Observation of actions appears to elicit spontaneous imagery in most people. Highlights: Imagery practice increased skill, strategy, and mastery imagery ability. Action observation increased skill, strategy, and mastery imagery ability. The control group did not improve skill, strategy, and mastery imagery ability. There were no increases in imagery ability of motivational content for any group.